On the geometry of non-classical curves - Hefez, Abramo; Kakuta, Neuza [UNESP] (Springer Nature, 1992)
In this paper we relate the numerical invariants attached to a projective curve, called the order sequence of the curve, to the geometry of the varieties of tangent linear spaces to the curve and to the Gauss maps of the curve. © 1992 Sociedade Brasileira de Matemática.